2007
DOI: 10.1111/j.1365-2567.2007.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus differentially activates murine myeloid and plasmacytoid dendritic cells

Abstract: Summary Respiratory syncytial virus (RSV) is the primary cause of bronchiolitis in young children. Upon infection both T helper 1 (Th1) and Th2 cytokines are produced. Because RSV‐induced Th2 responses have been associated with severe immunopathology and aggravation of allergic reactions, the regulation of the immune response following RSV infection is crucial. In this study we examined the influence of RSV on the activation and function of murine bone marrow‐derived dendritic cells (DCs). RSV induced the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…In the present study, we have provided data indicating that murine DCs are readily infected by RSV, which promotes their maturation. However, DC maturation was observed only in response to viable RSV and not UV-inactivated RSV, which would suggest that induction of DC maturation would need viral replication (25,32). In agreement with other reports, we observed significant secretion of IL-6 and IL-10 secretion by DCs infected with RSV (25,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we have provided data indicating that murine DCs are readily infected by RSV, which promotes their maturation. However, DC maturation was observed only in response to viable RSV and not UV-inactivated RSV, which would suggest that induction of DC maturation would need viral replication (25,32). In agreement with other reports, we observed significant secretion of IL-6 and IL-10 secretion by DCs infected with RSV (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, UV-RSV induced no significant up-regulation of maturation markers on DCs. These data are consistent with previous reports in human and murine DCs and support the notion that RSV replication might be required for DC maturation (25,32).…”
supporting
confidence: 93%
“…These findings suggest that Ag processing and presentation may be occurring in the lung periphery as well as in the draining lymph node. Indeed, a recent in vitro report using bone marrow-derived cDC showed that RSV infection led to activation and increased Ag-presenting function without a change in viability (39). The rapid and sustained decrease in the number of lung cDCs we see after respiratory viral infection may represent a general response to severe infection because it has also been observed in subjects with bacterial sepsis (40).…”
Section: Discussionmentioning
confidence: 95%
“…In particular, several laboratories have demonstrated that type I IFNs (mainly IFN-␣ and IFN-␤) and their major producers, plasmacytoid dendritic cells (pDCs), are important in protection from RSV disease. It has been reported that RSV stimulates pDCs isolated from human peripheral blood mononuclear cells (13,14) or murine bone marrow-derived pDCs (15,16) to produce type I IFNs ex vivo. Furthermore, several publications have demonstrated that RSV infection of adult mice induces pulmonary type I IFNs in vivo (17,18) and that intranasal administration of recombinant IFN-␣ significantly reduces the lung viral load, inflammation, weight loss, and clinical illness scores of RSVinfected adult mice (19).…”
mentioning
confidence: 99%